Fluidized Beds for Concentrated Solar Thermal Technologies—A Review - Tregambi, Claudio; Troiano, Maurizio; Montagnaro, Fabio; Solimene, Roberto; Salatino, Piero (Frontiers in Energy Research, 2021)
Fluidization displays a long record of success stories related to applications to thermal and thermochemical processes that may be associated to the unique properties of fluidized suspensions of solid particles and to the inherent flexibility of fluidized bed design and operation. Coupling fluidization with Concentrated Solar Power (CSP) is a stimulating cross-disciplinary field of investigation which poses challenging issues and great opportunities to fluidization scientists and technologists. In this article the current and perspective applications of fluidized beds to collection, storage and exploitation of solar radiation are surveyed. Novel and “creative” designs of fluidized bed solar receivers/reactors are reported and critically discussed. The vast field of applications of solar driven fluidized bed processes, from energy conversion with thermal energy storage, to solids looping for thermochemical energy storage, production of fuels, chemicals and materials, is explored with an eye at past and current developments and an outlook of future perspectives.